Respostas
respondido por:
1
F(x)=5x^4+3x^2+2x-1 e G(x)=2x^3+4x+3
F(x)+G(x)=5x^4+3x^2+2x-1+2x^3+4x+3 //Como é uma soma é só copiar os termos.
F(x)+G(x)=5x^4+2x^3+3x^2+6x+2
Obs:Apenas some aqueles que tiverem o mesmo grau no X.
F(x)+G(x)=5x^4+3x^2+2x-1+2x^3+4x+3 //Como é uma soma é só copiar os termos.
F(x)+G(x)=5x^4+2x^3+3x^2+6x+2
Obs:Apenas some aqueles que tiverem o mesmo grau no X.
respondido por:
1
F+G
5x^4 + 3x^2 - 2x - 1 + (2x^3 + 4x + 3)
5x^4 + 2x^3 + 3x^2 -2x +4x - 1 + 3
5x^4 + 2x^3 + 3x^2 + 2x + 2 ok!
5x^4 + 3x^2 - 2x - 1 + (2x^3 + 4x + 3)
5x^4 + 2x^3 + 3x^2 -2x +4x - 1 + 3
5x^4 + 2x^3 + 3x^2 + 2x + 2 ok!
Perguntas similares
7 anos atrás
7 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás